Heavy Metals and Probabilistic Risk Assessment via Pheretima (a Traditional Chinese Medicine) Consumption in China - Xu, Xiaohui; Li, Limin; Zhou, Heng; Hu, Qing; Wang, Lingling; Cai, Qiang; Zhu, Yin; Ji, Shen (Frontiers in Pharmacology, 2022)
Earthworms are known to accumulate inorganic contaminants from soil, but it can also be used as a traditional Chinese medicine (TCM) called Pheretima, which would cause safety problems with long-term exposure. Here, this study was to determine and analyze the level of heavy metal contamination for arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), manganese (Mn), nickel (Ni) and lead (Pb) in Pheretima and then explore the probabilistic health risks caused by 8 heavy metals in 98 batches of Pheretima with Monte Carlo simulation. A risk assessment strategy was conducted to assess heavy metal-associated health risk of Pheretima based on consumption data. For random consumption sampling, the results found that the non-carcinogenic risk of As is higher than the acceptable level and the carcinogenic risk levels of As and Cr exceeded the acceptable risk recommended by USEPA. Cr and As were regarded as the priority metals for risk control in the present study. Finally, it was recommended that the dosing frequency should be less than 24 d/y. In general, this study conducted a probabilistic risk assessment of heavy metals in Pheretima, which would be of significance for policy makers to take effective strategies to improve the quality and safety of Pheretima.